2019
DOI: 10.1016/j.pbb.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate pattern analysis of the neural correlates of smoking cue attentional bias

Abstract: The automatic capture of attention by drug cues, or attentional bias, is associated with craving and predicts future drug use. Despite its clinical significance, the neural bases of attentional bias to drug cues is not well understood. To address this gap, we undertook a neuroimaging investigation of the neural correlates of attentional bias towards smoking cues. Twenty-nine adults, including 14 active smokers and 15 non-smokers, completed a spatial cuing task during fMRI. A multivariate pattern analysis (MVPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…This was interpreted to mean that greater distraction by drug words (increased errors) required greater OFC suppression of an emotional response [33]. Attentional bias in smokers has also been linked to increased BOLD response in ACC, anterior insula, and OFC Area 13 [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…This was interpreted to mean that greater distraction by drug words (increased errors) required greater OFC suppression of an emotional response [33]. Attentional bias in smokers has also been linked to increased BOLD response in ACC, anterior insula, and OFC Area 13 [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Sociodemographic and psychometric variables were compared among groups with LSD t tests. We carried out multivariate pattern recognition analysis (Elton, Chanon, & Boettiger, 2019) to assess correlations between psychometric symptoms (i.e., AHRS, PANSS, HAMD, HAMA, and YMRS, MCCB, and GAF scores) and imaging data with a significance criterion of p < .05.…”
Section: Methodsmentioning
confidence: 99%
“…Education, y 16.1 (2.5) 12.0 (2.0) 14.0 (3.5) 16.1 (3.5) 10.0 (2.5) 15.0 (3.0) 12.0 (3. recognition analysis (Elton, Chanon, & Boettiger, 2019) to assess correlations between psychometric symptoms (i.e., AHRS, PANSS, HAMD, HAMA, and YMRS, MCCB, and GAF scores) and imaging data with a significance criterion of p < .05.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Elton, Chanon, and Boettiger (2019) , they used a multivariate pattern analysis (MVPA) to detect neural responses to nicotine addiction and neutral pictures. They found that the rostral ACC and IFG showed differences related to nicotine addiction in attentional bias neural correlates.…”
Section: Nicotine Addiction and Internet Gaming Disordermentioning
confidence: 99%